STEM-Based Learning Analysis to Improve Students’ Problem Solving Abilities in Science Subject: a Literature Review - Astuti, Nurul Heni; Rusilowati, Ani; Subali, Bambang (Journal of Innovative Science Education, 2021)
STEM is one of the learning paradigms that integrates science, technology, engineering and mathematics. The combination of several learning methods is implemented to make students achieve certain abilities, like problem solving skills. Problem solving becomes a very important part in learning because it can motivate students and make them having a better cognitive level. The purpose of this study is to describe the effect of STEM learning on physics material applied in schools to the problem-solving abilities of students. The method used in this research is meta-analysis where the researcher analyzed several articles as needed. Articles were limited to the last 5 years of publication, namely 2014 - 2019. Searching for articles used the Scholar, Eric, and Elsevier search engines. From the searching results, it was obtained 21 relevant articles according to the needs of researchers. Then, from 21 articles that were obtained as many as 86% were research articles that used questions or teaching materials as STEM-based learning media and 14% were review articles. The keywords used in the search were STEM, problem solving and physics. Based on the analysis conducted it can be concluded that learning through the STEM approach can improve students' problem solving abilities.